Violence at work - Chappell, Duncan; Di Martino, Vittorio (International Labour Office, 2006)
Provides a basis for understanding the nature of workplace violence and suggests ways of preventing it in the future. Focuses on those data, experiences and publications which best help to explain and interpret the roots of violence at work, and to promote proactive initiatives.